Pengaruh Literasi Keuangan, Risk Tolerance, Dan Experienced Regret Terhadap Pemilihan Jenis Investasi Keuangan Syariah Pada Generasi Millenial - Elmiliyani Wahyuni; Fitri Yenti; Rizal rizal; Asrul Gustomi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this study was to examine the effect of financial literacy, risk tolerance and experienced regret on the selection of types of Islamic financial investments in the millennial generation in Indonesia. This study used purposive sampling and convenience sampling there were 8,483,213 respondents and sampling using the Slovin formula with an error rate of 10% which obtained a sample of 100 respondents. The analysis technique uses multiple lieniar regression. The results showed that financial literacy affects the selection of Islamic financial investment types, while Risk Tolerance has no effect on the selection of Islamic financial investment types, and experienced regret has a positive and significant effect on the selection of Islamic investment types, and simultaneously the influence of financial literacy, Risk Tolerance and experienced regret affects the selection of Islamic investment types..